STUDY ON HAIRY ROOTS INDUCTION OF Cratoxylum pruniflorum Kurz VIA Agrobacterium rhizogenes - Huy, Nguyen Tran Phuoc; Quyen, Tran Nguyen Le; Trinh, Cao Hue; Quynh, Phan Diem; Loan, Ha Thi; Quan, Nguyen Dang (HUIT Journal of Science, 2024)
Cratoxylum pruniflorum Kurz is a wild plant that grows across our country, particularly in the northern mountainous provinces. In a popular folkway, it is used to make medicine and drinking water. Scientists recently discovered that C. pruniflorum Kurz contains a variety of biologically active compounds, including xanthones in the bark and roots, epigallocatechin gallate, and epicatechin gallate in the leaves, as well as tannins, terpenoids, saponins ... have antibacterial, antioxidant, and cytotoxic properties against cancer cell lines. In this study, perfoliate tissue was transgenic for hairy roots induction in vitro using Agrobacterium rhizogenes ATCC 15834 with a bacterial density of 4.104 CFU/mL, acetosyringone (AS) concentration of 100 µM, and a co-culture period of 72 hours yielded the highest average rate of hairy roots induction at 4.66% on SH medium without growth regulators. Two hairy root lines R1 and R2 were selected through PCR, in which the hairy root line R2 grew well on SH liquid medium with a fresh weight of 582.08 mg, an increase of 2.19 times compared to the original weight. The above results are the basis for further studies on C. pruniflorum Kurz.